(untitled) (Philippine Journal of Agricultural Economics, 2018)
The sugar industry is the life-giving force of the economy of Negros Occidental which contributes to more than half of the country’s total sugar production. The study aims to know the socio-economic status of sugarcane farmers in the province; evaluate their management practices on sugarcane production profitability based on the suitability and constraints exhibited by the major soil series grown to sugarcane, and to determine the effect of these farmers’ practices on the properties of the soils. A survey on twenty-five (25) farmers was conducted. FAO soil constraints and suitability analysis tool were used to identify the constraints and suitability of Guimbalaon, Isabela, Luisiana, San Manuel, and Silay soil series. Existing management practices of farmers like monocropping, burning of trashes, and intensive and inappropriate use of inputs such as fertilizers and pesticides may either affect soil physical, chemical, and biological properties. Topography and wetness were the severe constraints in all soil series. Sugarcane farmers with farms belonging to Silay series have the highest profitability based on net income, return on investment, and benefit-cost ratio while those belonging to Isabela series have the lowest profitability which could be attributed to varying constraints for sugarcane production thus, appropriate soil management interventions are necessary for this series.